Expectation vs. reality: How stereotypes and expectation disconfirmation affect job evaluations in online labor markets - Diana Tran Nhat; Timm Teubner (PLoS ONE, 2025)
In online labor markets, reputation determines both job opportunities and pay and even small disparities can translate into significant economic differences. While gender-related bias in reputational metrics such as likes, reviews, and ratings has been empirically documented, the mechanisms through which they arise remain insufficiently understood. This study presents results from an online experiment, varying workers’ gender, domain, and performance, to investigate how expectations about workers are formed and how they affect subsequent evaluations. Drawing on Expectation Disconfirmation Theory and Role Congruity Theory, we test whether the effect of disconfirmation (i.e., discrepancies between expected and actual performance) on evaluations varies with congruity (i.e., stereotypical fit between gender and domain). Contrary to our hypothesis, workers in congruent settings do not elicit higher expectations than those in incongruent roles. Similarly, the effect of positive and negative disconfirmation does not vary with congruity. However, exploratory analyses suggest that congruity does affect expectations and evaluations when individuals hold strong gender-domain associations. In case of stereotypical associations, individuals expect higher performance of workers in congruent domains and evaluate them more leniently if they fail to meet expectations. Our findings contribute to understanding why identical performances might be judged differently depending on gender-domain associations, expectations, and disconfirmation.